Optimal decarbonization strategies for an industrial port area by using hydrogen as energy carrier - Pivetta, Davide; Volpato, Gabriele; Carraro, Gianluca; Dall’Armi, Chiara; Da Lio, Luca; Lazzaretto, Andrea; Taccani, Rodolfo (International journal of hydrogen energy, 2024)
This article discusses possible strategies for decarbonizing the energy systems of an existing port. The approach consists in creating a complete superstructure that includes the use of renewable and fossil energy sources, the import or local production of hydrogen, vehicles and other equipment powered by Diesel, electricity or hydrogen and the associated refuelling and storage units. Two substructures are then identified, one including all these options, the other considering also the addition of the energy demand of an adjacent steel industry. The goal is to select from each of these two substructures the most cost-effective configurations for 2030 and 2050 that meet the emission targets for those years under different cost scenarios for the energy sources and conversion/storage units, obtained from the most reliable forecasts found in the literature. To this end, the minimum total cost of all the energy conversion and storage units plus the associated infrastructures is sought by setting up a Mixed Integer Linear programming optimization problem, where integer variables handle the inclusion of the different generation and storage units and their activation in the operational phases. The comprehensive picture of possible solutions set allows identifying which options can most realistically be realized in the years to come in relation to the different assumed cost scenarios. Optimization results related to the scenario projected to 2030 indicate the key role played by Diesel hybrid and electric systems, while considering the most stringent, or much more stringent, scenarios for emissions in 2050, almost all vehicles energy demand and industry hydrogen demand is met by hydrogen imported as ammonia by ship. •Energy/hydrogen demands of industry and port equipment/vehicles are considered.•32 optimization runs are performed under different cost and emission scenarios.•Optimal set of decarbonization strategies is selected for a real industrial port area.•Electrification/hybridization play a key role in medium/long-term decarbonization.•Hydrogen technologies ensure a deep decarbonization of the system in 2050.